Delayed cord clamping with stabilisation at all preterm births – feasibility and efficacy of a low cost technique. (May 2019) - Bates, Sarah E.; Isaac, Thomas C.W.; Marion, Rose L.; Norman, Victoria; Gumley, Joanna S.; Sullivan, Charlotte D.
Abstract: Objectives: Meta-analysis data suggests that Delayed cord clamping (DCC) in preterm infants is associated with a 32% reduction in mortality. Reported rates of this intervention are low, particularly for caesarean deliveries. Perceived difficulties providing respiratory support and thermal care during DCC may be barriers to implementation of this intervention. Commercially available equipment to facilitate this can be expensive. This study aimed to evaluate the feasibility and efficacy of a simple, low cost technique to deliver respiratory support and thermal care during DCC at all preterm deliveries (including caesarean), with the hypothesis that this could increase rates of preterm infants receiving DCC. Study design: Data was collected retrospectively from 46 infants born at <32 weeks gestation in 2015. The technique was introduced in early 2017, as part of a perinatal Quality Improvement project. Data was collected prospectively from 63 infants born at <32 weeks gestation in 2017-2018. Results: Rates of DCC in infants born <32 weeks gestation have increased from 12.5% in 2015 to 89.4% in 2017-2018. In 2017–2018, thermal care and respiratory support was provided to all infants who received DCC. Conclusion: Multidisciplinary perinatal team working allowed development of a simple, low cost technique to deliver DCC at all preterm deliveries. We have demonstrated feasibility and efficacy of this technique, and a significant and sustained improvement in rates of DCC in our preterm population. We hope that by sharing this approach, other centres will be able to implement a similar strategy, closing the gap between evidence base and translation into clinical practice, and allowing provision of DCC for preterm infants as a standard part of high quality perinatal care.